Menguak Minat Generasi “Z” di Denpasar Mengadopsi Qris - Putu Seli Dianawati; Putu Sri Arta Jaya Kusuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of perceived ease of use, perceived security, perceived benefits, social environment, and trust on the interest of Generation Z in Denpasar City to adopt QR Code Indonesian Standard (QRIS). Additionally, it examines the relationship between interest and the actual use of QRIS. The research is motivated by the significant potential of QRIS as a digital payment system among Generation Z, known as digital natives. The study employs a quantitative approach with a survey method. A sample of 384 respondents was selected using purposive sampling. Data analysis was conducted using structural equation modeling with partial least squares (SEM-PLS). The variables studied include perceived ease of use, security, benefits, social environment, trust, interest, and actual use of QRIS. The results indicate that perceived ease of use, security, benefits, social environment, and trust have a positive and significant effect on the interest in using QRIS. Moreover, interest significantly influences the actual use of QRIS. These findings suggest that ease of use, benefits, and security are the main predictors of QRIS adoption, while trust plays a crucial role in fostering user loyalty.